Attitude Towards Knowledge Sharing as a Mediator in Understanding the Impact of Extrinsic Motivation, Intrinsic Motivation, Other Motivations, and OCB on the Performance of Police Officers - ., Subhan; ., Samdin; Madjid, Rahmat; ., Juharsah; Junaiddin, Arsyad (International Journal of Membrane Science and Technology, 2023)
Leaders are crucial in influencing members’ motivation and improving organizational performance. In the National Police, member performance is vital to maintaining public trust. Motivations such as expected corporate rewards and satisfaction in knowledge sharing can influence knowledge-sharing behavior. Other factors, including confidence, leadership, and information technology, affect members’ knowledge-sharing abilities. Organizational Citizenship Behavior (OCB) reflects members’ commitment and positive contribution to the organization and is closely related to motivation and knowledge sharing. Therefore, improving performance through motivation, knowledge sharing, and OCB is crucial in the National Police, which upholds public security and order. This study investigates the role of attitude towards knowledge sharing in linking motivation, OCB, and Polri members’ performance in Southeast Sulawesi. By doing so, we hope to improve the service and image of the National Police. The literature review includes the Knowledge-Based View (KBV), which stresses the importance of knowledge in creating a competitive advantage. The Social Exchange Theory (SET) views employee behaviors as the result of social exchange and knowledge sharing.Extrinsic and intrinsic motivation are central to knowledge-sharing behavior, whereas OCB includes voluntary behavior that supports organizations. The research was conducted at the Regional Police Office of Southeast Sulawesi Province, involving members of the National Police. The study lasted for four months, with a sample of 338 people. Data was collected through questionnaires and interviews. The results of data analysis using the Structural Equation Model (SEM) method show that extrinsic motivation, intrinsic motivation, and other motivational factors influence knowledge-sharing attitudes in organizations. Organizational civic behavior also affects knowledge-sharing attitudes. The relationship between Motivation, OCB, and performance of members of the National Police is not direct, but instead through the mediation of knowledge-sharing attitudes. Therefore, knowledge-sharing is a crucial factor linking motivation and behavior with significant performance outcomes in the context of the National Police, supporting the effectiveness of such organizations in maintaining public security and order.